Graphite composite material and preparation method and application thereof

Through the preparation method of graphite composite materials, porous alumina doped titanium niobate coated graphite and reacted with organic lithium salt to form a double-coated structure of lithium titanium niobate and lithium metaaluminate, which solves the problem of fast negative electrode material of lithium ion battery The problem of insufficient charging performance and safety performance has achieved high-performance and safe lithium-ion battery materials.

CN119240686AActive Publication Date: 2025-01-03SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411371303.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The fast charging performance and first-time efficiency of the negative electrode materials of existing lithium-ion batteries are low, and there are problems of material circulation performance and safety hazards.

Method used

By using the preparation method of graphite composite materials, the co-deposition reaction of graphite, organic niobium source solution, organic titanium source solution, organic alkali and aluminum-based coupling agent is carried out to form a porous aluminum oxide-doped titanium niobate coated graphite material, and Heating reaction and sintering treatment with the organic lithium salt were prepared to prepare a double-coated graphite composite of lithium titanium niobate and lithium metaaluminate.

Benefits of technology

The fast charging performance, first-time efficiency and energy density of the material are significantly improved, while improving safety performance. The ion diffusion rate and voltage platform of the material are enhanced through the porous structure and the double-layer cladding structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240686A_ABST
    Figure CN119240686A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery material preparation, in particular to a graphite composite material and a preparation method and application thereof. According to the preparation method, an organic niobium source and an organic titanium source are subjected to in-situ synthesis through a chemical deposition method, titanium niobate is coated on the surface of graphite, meanwhile, aluminum hydroxide is obtained in situ through a reaction of organic alkali and an aluminum-based coupling agent, and then the porous aluminum oxide doped titanium niobate coated graphite composite material is obtained through subsequent carbonization treatment. Finally, through chemical reaction between organic lithium salt and the porous aluminum oxide doped titanium niobate coated graphite composite material and sintering treatment, the lithium titanium niobate and lithium metaaluminate double-coated graphite composite material which is good in fast charging performance, high in first efficiency and high in energy density is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery material preparation, and in particular to a graphite composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of lithium-ion battery technology, the energy density of batteries has been greatly improved. The market demand for shortening charging time is also increasing, requiring the negative electrode materials used in lithium-ion batteries to have fast charging performance while taking into account the energy density and high temperature performance of the materials. The fast charging performance of the battery mainly depends on the fast charging ability of its negative electrode material. Under charging conditions, the negative electrode, as an acceptor of lithium ions, needs to have the ability to quickly accept a large number of lithium ions for embedding. Otherwise, during the fast charging process, lithium ions will be deposited and precipitated on the surface of the negative electrode to form lithium dendrites, which may pierce the diaphragm and cause an internal short circuit, thus causing a safety hazard.

[0003] At present, graphite is a commonly used material for negative electrodes of lithium batteries, and the main measures to improve the fast charging performance of graphite negative electrode materials are: 1) coating soft carbon or hard carbon on the surface of graphite, but soft carbon / hard carbon itself has defects such as low specific capacity, low first efficiency, and low compaction density. Coating on the surface of graphite will limit the first efficiency of the material and its specific capacity; 2) doping metal oxides or non-metal oxides (such as iron oxide or silicon oxide materials) with high specific capacity into graphite negative electrode materials, but there is a defect of large expansion when fully charged, which leads to a serious decrease in the cycle performance of the material; 3) coating inorganic lithium salts on the surface of graphite to improve the ionic conductivity of the material, thereby achieving an improvement in the fast charging performance of the material, but there are problems of poor coating uniformity and limited improvement.

[0004] For example, the prior art discloses a fast-charging graphite composite material and a preparation method thereof, which mainly deposits inorganic lithium salt on its surface by a particle injection method. Although the fast-charging performance is improved to a certain extent, there are defects such as contact deviation between the inorganic lithium salt and the inner core, direct contact between the inorganic lithium salt and the electrolyte resulting in more side reactions, reduced initial efficiency and gas production, etc. Moreover, a single lithium salt is used for coating, which has limited improvement in the fast-charging performance and initial efficiency of the material.

[0005] Therefore, the existing graphite negative electrode materials still need to be improved. How to improve the electrochemical properties of graphite negative electrode materials, especially the fast charging performance and initial efficiency, is still a technical problem that needs to be solved urgently. Summary of the invention

[0006] Therefore, the technical problem to be solved by the present invention is to overcome the defect of poor electrochemical performance of existing carbon negative electrode materials, thereby providing a graphite composite material and a preparation method and application thereof that solve the above problem.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing a graphite composite material, comprising:

[0009] Graphite, an organic niobium source solution, an organic titanium source solution, an organic base, and an aluminum-based coupling agent are mixed for co-deposition reaction, and then subjected to solid-liquid separation and carbonization treatment to obtain a porous aluminum oxide-doped titanium niobate-coated graphite material;

[0010] The porous alumina-doped titanium niobate-coated graphite material is mixed with an organic lithium salt, heated and reacted in a liquid environment, and subjected to solid-liquid separation and sintering treatment to obtain a graphite composite material.

[0011] Preferably, the mass ratio of the graphite, the organic niobium source solution, the organic titanium source solution, the organic base, and the aluminum-based coupling agent is 100: (100-500): (100-500): (10-30): (1-5);

[0012] And / or, the mass ratio of the organic niobium source to the solvent in the organic niobium source solution is (10-30):500;

[0013] And / or, the mass ratio of the organic titanium source to the solvent in the organic titanium source solution is (10-30):500.

[0014] Preferably, the organic niobium source solution further includes a first dispersant; optionally, the mass ratio of the first dispersant to the solvent in the organic niobium source solution is (1-5):500; optionally, the first dispersant includes at least one of polyvinyl pyrrolidone, polyacrylonitrile and sodium dodecyl sulfonate;

[0015] And / or, the organic titanium source solution also includes a second dispersant; optionally, the mass ratio of the second dispersant to the solvent in the organic titanium source solution is (1-5):500; optionally, the second dispersant includes at least one of polyvinyl pyrrolidone, polyacrylonitrile, and sodium dodecyl sulfate.

[0016] Preferably, the mass ratio of the porous alumina-doped titanium niobate-coated graphite material to the organic lithium salt is 100:(5-15).

[0017] Preferably, the mixing process of the porous alumina-doped titanium niobate-coated graphite material and the organic lithium salt comprises: mixing the organic lithium salt with a solvent to obtain a lithium-containing solution; adding a third dispersant and the porous alumina-doped titanium niobate-coated graphite material to the lithium-containing solution and mixing them evenly;

[0018] Optionally, the mass percentage of the organic lithium salt in the lithium-containing solution is 1-10wt%;

[0019] Optionally, the mass ratio of the third dispersant to the porous alumina-doped titanium niobate-coated graphite material is (1-5): 100;

[0020] Optionally, the solvent in the lithium-containing solution includes N-methylpyrrolidone;

[0021] Optionally, the third dispersant comprises polyvinyl alcohol.

[0022] Preferably, the temperature of the co-deposition reaction is 150-250° C.; the duration of the co-deposition reaction is 2-12 hours;

[0023] And / or, the temperature of the carbonization treatment is 500-1000° C.; the duration of the carbonization treatment is 1-6 hours;

[0024] And / or, the temperature of the heating reaction is 50-150° C.; the duration of the heating reaction is 1-6 hours;

[0025] And / or, the temperature of the sintering treatment is 500-900° C.; the duration of the sintering treatment is 1-6 hours.

[0026] Preferably, the organic niobium source includes at least one of niobium ethoxide, niobium oxalate, and ammonium niobium oxalate;

[0027] And / or, the solvent in the organic niobium source solution includes an organic alcohol; optionally, the organic alcohol includes at least one of ethanol, isopropanol, and glycerol;

[0028] And / or, the solvent in the organic titanium source solution includes an organic alcohol; optionally, the organic alcohol includes at least one of ethanol, isopropanol, and glycerol;

[0029] And / or, the organic titanium source includes at least one of titanium tetraisopropoxide, titanium tetrafluoride, and butyl titanate;

[0030] and / or, the organic base comprises at least one of pyridine, imidazole, indole, pyrrole and derivatives thereof;

[0031] And / or, the aluminum-based coupling agent includes an aluminate coupling agent; optionally, the aluminate coupling agent includes at least one of aluminum triacetylacetonate, diisopropyl (acetylacetonate)aluminate, isopropyl distearoyloxyaluminate, diisopropyl (ethyl acetoacetate)aluminate, diisopropyl acetylacetonate aluminum complex, and isopropoxy distearoyloxyaluminate;

[0032] And / or, the organic lithium salt includes at least one of lithium acetate, lithium pyruvate, and lithium stearate;

[0033] And / or, the solid-liquid separation comprises filtration.

[0034] The present invention also provides a graphite composite material, which is prepared by the above-mentioned graphite composite material preparation method.

[0035] The present invention also provides a negative electrode material, comprising the above-mentioned graphite composite material.

[0036] The present invention also provides a secondary battery, comprising the above-mentioned negative electrode material.

[0037] The present invention also provides an electrical device, comprising the secondary battery.

[0038] The technical solution of the present invention has the following advantages:

[0039] The preparation method of the graphite composite material provided by the present invention comprises: mixing graphite, an organic niobium source solution, an organic titanium source solution, an organic base, and an aluminum-based coupling agent for co-precipitation reaction, and subjecting to solid-liquid separation and carbonization treatment to obtain a porous aluminum oxide doped titanium niobate coated graphite material; mixing the porous aluminum oxide doped titanium niobate coated graphite material with an organic lithium salt, heating the reaction in a liquid phase environment, and subjecting to solid-liquid separation and sintering treatment to obtain a graphite composite material. The present invention first synthesizes titanium niobate in situ and coats it on the graphite surface by chemical deposition method using an organic niobium source and an organic titanium source, and simultaneously obtains aluminum hydroxide in situ by reacting an organic base with an aluminum-based coupling agent, and then obtains a porous aluminum oxide doped titanium niobate coated graphite composite material through subsequent carbonization treatment, and finally obtains a lithium titanium niobate and lithium metaaluminate double-coated graphite composite material with good fast charging performance, high first efficiency, high energy density and good safety performance through a chemical reaction between an organic lithium salt and a porous aluminum oxide doped titanium niobate coated graphite composite material and sintering treatment. In the graphite composite material prepared by the present invention, lithium titanium niobate has the characteristics of large interlayer spacing, moderate specific capacity, high ion diffusion rate, high voltage platform, etc., while porous lithium aluminate itself has no specific capacity, but through interaction between it and lithium titanium niobate, the initial efficiency, rate performance and safety performance of the coating layer are significantly improved.

[0040] In addition, the present invention uses a chemical deposition method to carbonize and coat the organic niobium source and the organic titanium source on the graphite surface, which has the advantages of good uniformity, mild reaction conditions, high reaction efficiency, etc., and the organic compound generates a porous structure after carbonization, thereby improving the liquid retention performance of the material and achieving the technical effect of reducing expansion; at the same time, the organic base reacts with the aluminum-based coupling agent under alkaline conditions (Al 3+ +OH - =Al(OH) 3 ), Al(OH) 3In the subsequent high-temperature carbonization process, porous aluminum oxide is generated and doped in the titanium niobate material, and its porous structure can also improve the liquid retention performance of the material. Secondly, the aluminum-based coupling agent in the present invention also provides a coupling effect to enhance the bonding force between the niobium source, the titanium source and the graphite material while reacting with the organic base, thereby further improving the initial efficiency and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0042] Figure 1 This is a SEM morphology image of the graphite composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0043] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0044] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0045] Example 1

[0046] This embodiment provides a method for preparing a graphite composite material, and the specific steps are as follows:

[0047] 1) Weigh 20 g of niobium ethanol and 3 g of polyvinyl pyrrolidone (CAS No.: 9003-39-8; Manufacturer: Boai New Open Source Pharmaceutical Co., Ltd.; Model: K17; Molecular weight: 10,000-16,000) and add them to 500 g of ethanol organic solvent and disperse them evenly to prepare an organic niobium source solution;

[0048] 2) Weigh 20 g of titanium tetraisopropoxide and 3 g of polyvinyl pyrrolidone and add them to 500 g of ethanol organic solvent and disperse them evenly to prepare an organic titanium source solution;

[0049] 3) 100 g of artificial graphite, 300 g of the organic niobium source solution of step 1), 300 g of the organic titanium source solution of step 2), 20 g of pyridine, and 3 g of aluminum triacetylacetonate were mixed and dispersed uniformly, and then co-precipitated at 200° C. for 7 h, and then filtered, and the obtained filter residue was carbonized at 800° C. for 3 h to obtain a porous alumina-doped titanium niobate-coated graphite material;

[0050] 4) Weigh 10g of lithium acetate and add it to N-methylpyrrolidone to prepare a 5wt% lithium-containing solution, then add 3g of polyvinyl alcohol (CAS: 9002-89-5; manufacturer: Sichuan Lai Te Ju Xin Pharmaceutical Excipients Co., Ltd.; model: 8805; molecular weight: 10,000-100,000) and 100g of the porous alumina-doped titanium niobate-coated graphite material of step 3) and disperse them evenly, then react at a temperature of 100°C for 3h, filter, and sinter the resulting filter residue at 600°C for 3h to obtain a lithium titanium niobate and lithium aluminate double-coated graphite composite material.

[0051] Example 2

[0052] This embodiment provides a method for preparing a graphite composite material, and the specific steps are as follows:

[0053] 1) Weigh 10 g of niobium oxalate and 1 g of polyacrylonitrile (CAS: 25014-41-9; manufacturer, Wuhan Rongcan Biotechnology Co., Ltd.; model, 89; molecular weight, 15,000) and add them to 500 g of isopropanol organic solvent and disperse them evenly to prepare an organic niobium source solution;

[0054] 2) Weigh 10 g of titanium tetrafluoride and 1 g of polyacrylonitrile and add them to 500 g of isopropanol organic solvent and disperse them evenly to prepare an organic titanium source solution;

[0055] 3) 100 g of artificial graphite, 100 g of the organic niobium source solution of step 1), 100 g of the organic titanium source solution of step 2), 10 g of imidazole, and 1 g of diisopropyl (acetylacetone) aluminate were mixed and dispersed uniformly, and then co-precipitated at 150° C. for 12 h, and then filtered, and the obtained filter residue was carbonized at 500° C. for 6 h to obtain a porous alumina-doped titanium niobate-coated graphite material;

[0056] 4) Weigh 5 g of lithium pyruvate and add it to N-methylpyrrolidone to prepare a 1 wt% lithium-containing solution, then add 1 g of polyvinyl alcohol and 100 g of the porous alumina-doped titanium niobate-coated graphite material of step 3) and disperse them evenly, then react at a temperature of 50°C for 6 h, filter, and sinter the resulting filter residue at 500°C for 6 h to obtain a lithium titanium niobate and lithium aluminate double-coated graphite composite material.

[0057] Example 3

[0058] This embodiment provides a method for preparing a graphite composite material, and the specific steps are as follows:

[0059] 1) Weigh 30 g of ammonium niobium oxalate and 5 g of sodium dodecyl sulfonate and add them to 500 g of glycerol organic solvent and disperse them evenly to prepare an organic niobium source solution;

[0060] 2) Weigh 30 g of butyl titanate and 5 g of sodium dodecyl sulfonate and add them to 500 g of isopropanol organic solvent and disperse them evenly to prepare an organic titanium source solution;

[0061] 3) 100 g of artificial graphite, 500 g of the organic niobium source solution of step 1), 500 g of the organic titanium source solution of step 2), 30 g of indole, and 5 g of isopropyl distearoyloxyaluminate were mixed and dispersed uniformly, and then co-precipitated at 250° C. for 2 h, and then filtered, and the obtained filter residue was carbonized at 1000° C. for 1 h to obtain a porous alumina-doped titanium niobate-coated graphite material;

[0062] 4) Weigh 15g of lithium stearate and add it to N-methylpyrrolidone to prepare a 10wt% lithium-containing solution, then add 5g of polyvinyl alcohol and 100g of the porous alumina-doped titanium niobate-coated graphite material of step 3) and disperse them evenly, then react at a temperature of 150°C for 1h, filter, and sinter the resulting filter residue at 900°C for 1h to obtain a lithium titanium niobate and lithium aluminate double-coated graphite composite material.

[0063] Example 4

[0064] This embodiment provides a method for preparing a graphite composite material, and the specific steps are as follows:

[0065] 1) Weigh 15 g of niobium ethoxide and 2 g of polyvinyl pyrrolidone and add them to 500 g of ethanol organic solvent and disperse them evenly to prepare an organic niobium source solution;

[0066] 2) Weigh 15 g of titanium tetraisopropoxide and 2 g of polyvinyl pyrrolidone and add them to 500 g of ethanol organic solvent and disperse them evenly to prepare an organic titanium source solution;

[0067] 3) 100 g of artificial graphite, 200 g of the organic niobium source solution of step 1), 200 g of the organic titanium source solution of step 2), 15 g of pyrrole, and 2 g of isopropoxy distearate acyloxyaluminate were mixed and dispersed uniformly, and then co-precipitated at 180° C. for 10 h, and then filtered, and the obtained filter residue was carbonized at 600° C. for 2 h to obtain a porous alumina-doped titanium niobate-coated graphite material;

[0068] 4) Weigh 8 g of lithium acetate and add it to N-methylpyrrolidone to prepare a 3 wt% lithium-containing solution, then add 2 g of polyvinyl alcohol and 100 g of the porous alumina-doped titanium niobate-coated graphite material of step 3) and disperse evenly, then react at 75°C for 2 h, filter, and sinter the resulting filter residue at 550°C for 2 h to obtain a lithium titanium niobate and lithium aluminate double-coated graphite composite material.

[0069] Example 5

[0070] This embodiment provides a method for preparing a graphite composite material, and the specific steps are as follows:

[0071] 1) Weigh 25 g of niobium ethoxide and 4 g of polyvinyl pyrrolidone and add them to 500 g of ethanol organic solvent and disperse them evenly to prepare an organic niobium source solution;

[0072] 2) Weigh 25 g of titanium tetraisopropoxide and 4 g of polyvinyl pyrrolidone and add them to 500 g of ethanol organic solvent and disperse them evenly to prepare an organic titanium source solution;

[0073] 3) 100 g of artificial graphite, 400 g of the organic niobium source solution of step 1), 400 g of the organic titanium source solution of step 2), 25 g of pyridine, and 4 g of diisopropoxy acetoacetic acid oleate aluminate were mixed and dispersed uniformly, and then co-precipitated at 230° C. for 5 h, and then filtered, and the obtained filter residue was carbonized at 900° C. for 4 h to obtain a porous alumina-doped titanium niobate-coated graphite material;

[0074] 4) Weigh 13 g of lithium acetate and add it to N-methylpyrrolidone to prepare an 8 wt% lithium-containing solution, then add 4 g of polyvinyl alcohol and 100 g of the porous alumina-doped titanium niobate-coated graphite material of step 3) and disperse them evenly, then react at a temperature of 125°C for 4 hours, filter, and sinter the resulting filter residue at 800°C for 4 hours to obtain a lithium titanium niobate and lithium aluminate double-coated graphite composite material.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 1 is that step 4) is not performed, and the porous alumina-doped titanium niobate-coated graphite material prepared in step 3) is directly used as the negative electrode material.

[0077] Comparative Example 2

[0078] This comparative example provides a method for preparing a graphite composite material, and the specific steps are as follows:

[0079] 10g of lithium acetate was added to 200g of N-methylpyrrolidone to prepare a 5wt% solution, and then 3g of polyvinyl alcohol dispersant was added, and 100g of graphite material was added and dispersed evenly, and reacted at a temperature of 800°C for 3h, filtered, and the obtained filter residue was sintered at 600°C for 3h to obtain a lithium-doped amorphous carbon-coated graphite composite material.

[0080] Comparative Example 3

[0081] The difference between this comparative example and Example 1 is that niobium ethoxide, titanium tetraisopropoxide and pyridine are replaced by niobium oxide, titanium oxide and deionized water, and other conditions are the same as those in Example 1.

[0082] Comparative Example 4

[0083] This comparative example provides a method for preparing a graphite composite material, and the specific steps are as follows:

[0084] 1) 100 g of artificial graphite, 11.47 g of niobium ethoxide, 11.47 g of titanium tetraisopropoxide, 3.44 g of polyvinyl pyrrolidone, 574 g of ethanol, 20 g of pyridine, and 3 g of aluminum triacetylacetonate were mixed and dispersed uniformly for co-precipitation reaction, and then filtered, and the obtained filter residue was carbonized at 800° C. for 3 h to obtain a porous alumina-doped titanium niobate-coated graphite material;

[0085] 2) Weigh 10 g of lithium acetate and add it to 200 g of N-methylpyrrolidone to prepare a 5 wt% lithium-containing solution, then add 3 g of polyvinyl alcohol and 100 g of the porous alumina-doped titanium niobate-coated graphite material of step 1) and disperse evenly, then react at a temperature of 100° C. for 3 h, filter, and sinter the resulting filter residue at 600° C. for 3 h to obtain a lithium titanium niobate and lithium aluminate double-coated graphite composite material.

[0086] Comparative Example 5

[0087] The difference between this comparative example and Example 1 is that the organic base (pyridine) is replaced by an inorganic base (sodium carbonate) of equal mass, and the other conditions are the same as those in Example 1.

[0088] Comparative Example 6

[0089] The difference between this comparative example and Example 1 is that the aluminate coupling agent (aluminum triacetylacetonate) is replaced by an equal mass of a titanate coupling agent (titanium acetylacetonate), and other conditions are the same as those in Example 1.

[0090] Test Case

[0091] (1) SEM test

[0092] The lithium titanium niobate and lithium aluminate double-coated graphite composite material prepared in Example 1 was subjected to SEM testing. The results are as follows: Figure 1 As shown by Figure 1It can be seen that the obtained composite material is granular, with an average particle size D50 of about 10 μm and a uniform size distribution.

[0093] (2) Diffusion coefficient and OI value test

[0094] The diffusion coefficients of the powder materials of the graphite composite materials prepared in the examples and comparative examples were tested by GITT, and the OI values ​​of the powder materials were tested by XRD. The test results are shown in Table 1.

[0095] (3) Button battery test

[0096] The graphite composite materials prepared in the embodiment and the comparative example were assembled into button batteries according to the following method:

[0097] Add binder, conductive agent and solvent to the negative electrode material, stir and mix to make negative electrode slurry, and coat the negative electrode slurry on copper foil (single surface density 6 mg / cm 2 ), drying, rolling, and cutting to obtain the negative electrode sheet. The binder is LA132 binder, the conductive agent is SP conductive agent, the solvent is double distilled water, and the weight ratio of the negative electrode material, SP conductive agent, LA132 binder and double distilled water is 95:1:4:220. The metal lithium sheet is used as the counter electrode, polyethylene propylene (PEP) is used as the separator, and LiPF 6 / EC+DEC(LiPF 6 The concentration of EC was 1.1 mol / L, the volume ratio of EC to DEC was 1:1) as the electrolyte, and the CR2032 button cell was assembled in an argon-filled glove box.

[0098] The button cells were installed on the Wuhan Blue Electric CT2001A battery tester, and charged and discharged at a rate of 0.1C. The charge and discharge voltage range was 0.005V to 2.0V, and the first discharge capacity and first discharge efficiency were measured. The 2C rate discharge capacity was tested, and its rate performance (2C / 0.1C) and cycle performance (0.2C / 0.2C, 100 weeks) were calculated. The test results are shown in Table 1:

[0099] Table 1

[0100]

[0101] As can be seen from Table 1, the discharge capacity, first efficiency and diffusion coefficient of the lithium titanium niobate and lithium aluminate coated graphite composite materials prepared in Examples 1-5 are significantly higher than those in Comparative Examples 1-6; the reason may be that the coating layer contains lithium aluminate, which has a high specific capacity and provides lithium ions during the first charge and discharge process, reduces the irreversible capacity, improves the first efficiency, and relies on the large interlayer spacing of niobium and titanium to improve the diffusion coefficient. At the same time, lithium aluminate has an inert characteristic with the electrolyte, reduces the irreversible capacity loss, and improves the first efficiency.

[0102] (3) Soft pack battery test

[0103] The negative electrode was prepared by using the lithium titanium niobate and lithium aluminate coated graphite composite materials prepared in Examples 1-5 and Comparative Examples 1-6, respectively. 1 / 3 Co 1 / 3 Ni 1 / 3 O 2 ) as the positive electrode, LiPF 6 (The solvent is EC+DEC (volume ratio 1:1), concentration 1.1 mol / L) as the electrolyte, celegard2400 as the separator, and a 2Ah soft-pack battery was prepared.

[0104] When preparing the negative electrode, a binder, a conductive agent, and a solvent are added to the negative electrode material, and the mixture is stirred and mixed to form a negative electrode slurry. The negative electrode slurry is coated on a copper foil (negative electrode single surface density 9.5 mg / cm 2 ), drying, roller pressing (compacted density 1.6g / cm 3 ), and cut to obtain a negative electrode sheet. The binder is LA136D binder, the conductive agent is SP conductive agent, the solvent is double distilled water, and the weight ratio of the negative electrode material, SP conductive agent, LA136D binder and double distilled water is 95:1:4:250.

[0105] When preparing the positive electrode, a binder solution is prepared, and then a conductive agent and a positive electrode material are added, and the mixture is stirred and mixed to form a positive electrode slurry. The positive electrode slurry is coated on an aluminum foil (single-sided surface density 20 mg / cm 2 ), drying, roller pressing (compacted density 3.4g / cm 3 ), cut to obtain a positive electrode sheet, the binder is PVDF, the conductive agent is SP, and the solvent is N-methylpyrrolidone. The weight ratio of the positive electrode material, the conductive agent, the binder and the solvent is 97:1:2:140.

[0106] 3.1 Cycle performance:

[0107] The battery cycle performance was tested at a charge and discharge rate of 1C / 1C, a voltage range of 2.8V-4.2V, and a temperature of 25±3°C. The test results are shown in Table 2.

[0108] 3.2x rate performance:

[0109] The battery was charged to 4.2V at a constant current rate of 1C, 2C, 3C or 5C, and then charged to 100% SOC in constant voltage mode (0.1C to 4.2V, 3h). The constant current ratio = constant current capacity / (constant current capacity + constant voltage capacity) was calculated. The test results are shown in Table 2.

[0110] Table 2

[0111]

[0112] The cycle performance and fast charging performance of the soft-pack battery prepared by the negative electrode material obtained in Table 2 are compared. It can be seen from the table that the cycle performance and fast charging performance (constant current ratio) of the embodiment battery are significantly better than those of the comparative example. The reason is that the material of the embodiment has a lower OI value and its excellent diffusion coefficient (as shown in Table 1), which improves the fast charging performance of the material; at the same time, the outer layer coated with lithium titanium niobate has an excellent large interlayer spacing to reduce expansion and improve the cycle performance of the battery.

[0113] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing a graphite composite material, characterized in that: include: Graphite, an organic niobium source solution, an organic titanium source solution, an organic base, and an aluminum-based coupling agent are mixed for co-deposition reaction, and then subjected to solid-liquid separation and carbonization treatment to obtain a porous aluminum oxide-doped titanium niobate-coated graphite material; The porous alumina-doped titanium niobate-coated graphite material is mixed with an organic lithium salt, heated and reacted in a liquid environment, and subjected to solid-liquid separation and sintering treatment to obtain a graphite composite material.

2. The method for preparing the graphite composite material according to claim 1, characterized in that: The mass ratio of the graphite, the organic niobium source solution, the organic titanium source solution, the organic base, and the aluminum-based coupling agent is 100: (100-500): (100-500): (10-30): (1-5); and / or, the mass ratio of the organic niobium source to the solvent in the organic niobium source solution is (10-30):500; And / or, the mass ratio of the organic titanium source to the solvent in the organic titanium source solution is (10-30):

500.

3. The method for preparing the graphite composite material according to claim 1, characterized in that: The organic niobium source solution further includes a first dispersant; optionally, the mass ratio of the first dispersant to the solvent in the organic niobium source solution is (1-5):500; optionally, the first dispersant includes at least one of polyvinyl pyrrolidone, polyacrylonitrile, and sodium dodecyl sulfonate; And / or, the organic titanium source solution also includes a second dispersant; optionally, the mass ratio of the second dispersant to the solvent in the organic titanium source solution is (1-5):500; optionally, the second dispersant includes at least one of polyvinyl pyrrolidone, polyacrylonitrile, and sodium dodecyl sulfate.

4. The method for preparing the graphite composite material according to claim 1, characterized in that: The mass ratio of the porous alumina-doped titanium niobate-coated graphite material to the organic lithium salt is 100:(5-15).

5. The method for preparing the graphite composite material according to claim 4, characterized in that: The mixing process of the porous aluminum oxide doped titanium niobate coated graphite material and the organic lithium salt comprises: mixing the organic lithium salt with a solvent to obtain a lithium-containing solution; adding a third dispersant and the porous aluminum oxide doped titanium niobate coated graphite material to the lithium-containing solution and mixing them uniformly; Optionally, the mass percentage of the organic lithium salt in the lithium-containing solution is 1-10wt%; Optionally, the mass ratio of the third dispersant to the porous alumina-doped titanium niobate-coated graphite material is (1-5): 100; Optionally, the solvent in the lithium-containing solution includes N-methylpyrrolidone; Optionally, the third dispersant comprises polyvinyl alcohol.

6. The method for preparing the graphite composite material according to claim 1, characterized in that: The temperature of the co-deposition reaction is 150-250° C.; the duration of the co-deposition reaction is 2-12 hours; And / or, the temperature of the carbonization treatment is 500-1000° C.; the duration of the carbonization treatment is 1-6 hours; And / or, the temperature of the heating reaction is 50-150° C.; the duration of the heating reaction is 1-6 hours; And / or, the temperature of the sintering treatment is 500-900° C.; the duration of the sintering treatment is 1-6 hours.

7. The method for preparing a graphite composite material according to any one of claims 1 to 6, characterized in that: The organic niobium source includes at least one of niobium ethoxide, niobium oxalate, and ammonium niobium oxalate; And / or, the solvent in the organic niobium source solution includes an organic alcohol; optionally, the organic alcohol includes at least one of ethanol, isopropanol, and glycerol; And / or, the solvent in the organic titanium source solution includes an organic alcohol; optionally, the organic alcohol includes at least one of ethanol, isopropanol, and glycerol; And / or, the organic titanium source includes at least one of titanium tetraisopropoxide, titanium tetrafluoride, and butyl titanate; and / or, the organic base comprises at least one of pyridine, imidazole, indole, pyrrole and derivatives thereof; And / or, the aluminum-based coupling agent includes an aluminate coupling agent; optionally, the aluminate coupling agent includes at least one of aluminum triacetylacetonate, diisopropyl (acetylacetonate)aluminate, isopropyl distearoyloxyaluminate, diisopropyl (ethyl acetoacetate)aluminate, diisopropyl acetylacetonate aluminum complex, and isopropoxy distearoyloxyaluminate; And / or, the organic lithium salt includes at least one of lithium acetate, lithium pyruvate, and lithium stearate; And / or, the solid-liquid separation comprises filtration.

8. A graphite composite material, characterized in that: The graphite composite material is prepared by the preparation method of any one of claims 1 to 7.

9. A negative electrode material, characterized in that: The graphite composite material comprises the graphite composite material as claimed in claim 8.

10. A secondary battery, characterized in that: Comprising the negative electrode material according to claim 9.

Citation Information

Patent Citations

  • Preparation method of carbon modified titanium niobate material, carbon modified titanium niobate material, and lithium ion capacitor and negative electrode paste thereof

    CN108183039A

  • Titanium niobate coated hard carbon composite material and preparation method thereof

    CN114094070A

  • Titanium niobate composite material, preparation method thereof, negative plate and battery

    CN118324183A

  • Low-temperature lithium ion battery negative electrode material as well as preparation method and application thereof

    CN118439602A

  • Lithium niobate coated graphite composite negative electrode material and preparation method and application thereof

    CN118712346A